Desarrollo de plantas de Schizolobium parahybum (Vell.) S.F.Blake (pachaco) aplicando diferentes tratamientos de fertilización a nivel de vivero en la parroquia La Unión, cantón Quinindé, provincia de Esmeraldas. - Cahuano Santamaria, Gladys Magdalena (2021)
The present investigation that was carried out in the La Unión parish of the Quinindé canton, Esmeralda province, aims to evaluate the development of Schizolobium parahybum (Vell.) S.F.Blake applying different fertilization treatments at the nursery level. Therefore, the methodology that was applied was a Completely Random Design; For the treatments, 2 Nitrofosca fertilizers (T1), Calciboro (T2) and a control (T0) were used to evaluate the development of the species and a sampling of 300 seedlings. The results obtained indicate that there were no significant differences in the study variables in height, diameter and number of leaves, despite this the T2 (Calciboro) indicates that I achieved better results in the variables that were evaluated, the survival of the seedlings was the one that stood out the most with a percentage of 77%, comparison of height in T (9.33), comparison in diameter in T (1.82), comparison of number of leaves in T (1.92); average height in cm per treatment (15.39). What concerns that the T2 stood out more in the morphological development of the seedlings towards the other treatments. Keywords: Treatments, Fertilizers, Nursery, Seedlings